Sales Promotion, Online Customer Review Feature, and Their Impact on Generation Z’s Impulse Buying Behavior: Evidence from Shopee Users - Maharani Rasyidfa Clara Putri; Tri Murwaningsih (APPS Publications, 2026)
This study aims to determine (1) the effect of sales promotions on the Shopee e-commerce platform on Gen Z’s impulsive buying behavior, (2) the effect of online customer review feature on the Shopee e-commerce platform on Gen Z’s impulsive buying behavior, (3) the effect of sales promotions and online customer review feature together on the Shopee e-commerce platform on Gen Z’s impulsive buying behavior. This study employs a quantitative causal approach using data collected through a questionnaire. The sampling technique was carried out by cluster random sampling with a sample of 178 Office Administration Education Students, FKIP UNS, Class of 2022-2025. Data processing used multiple linear regression through IBM SPSS Statistic 27 software. The results of the study show that sales promotions and online customer review feature both simultaneously and individually have a significant influence on the impulsive purchasing behavior of Generation Z students in the Office Administration Education Program at the Faculty of Teacher Training and Education, UNS. This indicates that more frequent promotions and more positive online reviews will increase the tendency toward impulsive purchasing behavior. This study focuses on Gen Z students in the Office Administration Education program at the Faculty of Teacher Training and Education (FKIP), UNS, as active users of the Shopee e-commerce platform. Most studies to date have examined sales promotions and online customer review feature.